(NlEONID aNDREEW(B. (NsOBRANIE SO^INENIJ W [ESTI TOMAH (B/s - (NaNDREEW(B, (NlEONIDs ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1990)
(NsOBRANIE SO^INENIJ W [ESTI TOMAH(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs; (NpXESYs